Budaya Egalitarian Pemerintah Desa dalam Perbaikan Badan Usaha Milik Desa (BUMDes) - Rahmatiah Rahmatiah; Dondick W. Wiroto; Zulaecha Ngiu; Salfa Boki; Salma Rivani Luawo (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
The purpose of this study is to describe the egalitarian cultural problems of the concept of BUMDes power in North Gorontalo Regency. The methods used qualitative research methods. Based on the results of the study it was found that; (1) The mindset of the community is still minimal in making product innovations from their natural and cultural wealth; (2) The entrepreneurship program supported by the Village Fund has not been able to encourage increased changes in the economic growth of the village, and (3) There has been no cooperation with external parties in building a market network to sell innovative products. So it can be concluded that, the concept of egalitarian culture towards changes in the bureaucracy of BUMDes can be carried out if it gets support from business actor agents.